Diaohua Chang in food court setting in Klang Valley, Malaysia / Chin Ee Ven - Chin, Ee Ven (2015)
Diaohua Chang is a place that provides nightly singing performance for the Chinese community in Malaysia. The overwhelming majority of male crowd can purchase flower garlands for the female singers as gratuity. This research focused on Diaohua Chang at the open-air food court where the singers perform mainly Chinese songs for the customers who are having their drinks or food. The gap of research was discovered after reviewing the literature of ethnomusicology, Chinese popular music, Chinese performing arts in Malaysia and other related researches. Diaohua Chang music performance which is part of the culture of Malaysian Chinese community was absent in the literature. In order to fill in the gap of research, this research looked into the characteristic, the performance style, the gender biased performers, and the customers’ organization of attention of Diaohua Chang. The main research method is ethnography based on phenomenology as its conceptual framework. Participant observation, interview sessions and virtual fieldwork were conducted to investigate the nature, the performances, and the cultural perspectives of Diaohua Chang. Four most popular Diaohua Chang at the food court of Klang Valley were selected for the fieldwork. Research findings revealed the trend of Chinese shidaiqu performance and the sexualization of the female performers in Diaohua Chang.